Evaluation of the Effectiveness of Swimming Pool Position as a Tuned Liquid Damper in Reducing the Drift Rasio Due to Earthquake Excitation with Response Spectrum Analysis - Tuasikal, Nur Risa Cahyana; Supriadi, Bambang; Siswosukarto, Suprapto (ASTONJADRO, 2025)
Swimming pools integrated with the main structure are increasingly popular in modern high-rise buildings due to their aesthetic appeal and recreational value. As a result, there has been much research into the influence of swimming pools, which were previously considered as additional masses, now function as passive dampers, Tuned Liquid Dampers (TLD). The focus of the research is the optimal placement of the swimming pool position because the swimming pool can increase the eccentricity to the center of mass, which affects the dynamic behavior of the building. This study analyzes the position of the swimming pool to affect the TLD’s effectiveness in reducing the drift ratio. The study was conducted numerically with ETABS at a 10-story hotel with two basements and a total building height of 39.6 meters. The swimming pool measuring 16.25 x 4.85 x 1.5 meters was analyzed in empty conditions and two positions, namely Pool P1 (existing pool) with a mass eccentricity of 20.679 m. In contrast, pool P2 is a pool with a position that is moved closer to the center of mass, with a mass eccentricity of 10.650 m. The swimming pool is modeled with a spring-mass model as a dynamic load, and the damping ratio is 5%. The analysis used the mass spectrum response method based on SNI 1726:2019.